A mutation-led search for novel functional domains in MeCP2. (27th April 2018) - Guy, Jacky; Alexander-Howden, Beatrice; FitzPatrick, Laura; DeSousa, Dina; Koerner, Martha V; Selfridge, Jim; Bird, Adrian
Abstract: Most missense mutations causing Rett syndrome (RTT) affect domains of MeCP2 that have been shown to either bind methylated DNA or interact with a transcriptional co-repressor complex. Several mutations, however, including the C -terminal truncations that account for ∼10% of cases, fall outside these characterized domains. We studied the molecular consequences of four of these 'non-canonical' mutations in cultured neurons and mice to see if they reveal additional essential domains without affecting known properties of MeCP2. The results show that the mutations partially or strongly deplete the protein and also in some cases interfere with co-repressor recruitment. These mutations therefore impact the activity of known functional domains and do not invoke new molecular causes of RTT. The finding that a stable C -terminal truncation does not compromise MeCP2 function raises the possibility that small molecules which stabilize these mutant proteins may be of therapeutic value.